Gymnastics : skills, techniques, training - Readhead, Lloyd (Ramsbury, Marlborough, Wiltshire [England] : Crowood Press, 2011)
Provides an introduction to artistic gymnastics, discussing the training and technical skills needed in both men's and women's gymnastics and the role of coaching, psychology, and nutrition in a safe and progressive training regime.
Includes index.
Keywords: Artistic gymnastics; Gynmastics; Gymnastics